Masker Air Leri Dan Greentea Untuk Perawatan Kulit Kusam - Agus Susanti; Lailatun Nasikhah; Ari Fatikhatuz Zulva; Sefira Maharani (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2021)
Dull skin is a skin condition that is full of dead skin cells. The cause of dull skin is due to lack of water supply, pollution and sunlight and lack of facial care. Facial care can be done using a face mask. Facial masks are treatments intended to treat facial skin. Rice water is obtained from washing rice. Cherry water contains vitamins that are beneficial for skin health. Greentea has antioxidants that are good for skin health. The abundant content of EGCG antioxidants in greentea has the ability to rejuvenate damaged skin cells. The aim of this research is to create a mask based on leri and greentea water which functions to treat dull skin. The research method used is descriptive qualitative. Data collection methods used are literature, interviews, experiments and documentation. The experiment was carried out at the Laboratory of the Make-Up Study Program of the Kartini Academy of Social Welfare, Jalan Sultan Agung, No. 77, Gajahmungkur Village, Gajah Mungkur District, Semarang City. The experiment was carried out 3 times with the composition of (1) 15 grams of water powder and 10 grams of greantea, (2) 15 grams of water powder and 15 grams of grentea, (3) 10 grams of water powder and 15 grams of grenteea. From the results of these three experiments, this experiment produced a mask with a green color, coarse texture and a fresh scent of greentea.